General and Specific Cheating Strategies at School - Rost, Detlef H.; Sparfelott, Jam; Narkevičienė, Bronė (Acta Paedagogica Vilnensia, 2004)
This study aims to shed some light on the dimensional structure of cheating at school. N=524 students from 25 German grammar school classes (grade 8 to 10) are investigated. Principal component analysis yield four specific components of cheating behaviour. Two of them are independent of school subjects. The other two are related to the fields of mathematics/physics and (native German) language/history. Validity data (negative relations to scholastic achievement, academic self-concept, interests in school subjects) are in accordance with theory. A general (not subject-specific) cheating questionnaire could be predicted well by the four specific cheating components (R2=.64).